Complex relationships between structural changes using brain Magnetic Resonance imaging in early diagnosis of Alzheimer's Disease (2014)
Neurodegenerative disease is the term used for a sort of incurable pathologies present in the brain. It results in progressive degeneration of nerve cells, leading to movement ata- xias, or mental dementias. Dementias are responsible for greatest burden of disease with Alzheimer's representing approximately 60-70% of cases. The main goal of this thesis is to highlight subtle anatomical differences that constitute abnormal structural patterns that may indicate the presence or absence of the pathology in regions with similar visual features by using Brain Magnetic Resonance Imaging.